Investigating the Benefits of Scaffolding in Assessments of Young English Learners: A Case for Scaffolded Retell Tasks. Issue 2 (15th March 2019) - Choi, Ikkyu; Wolf, Mikyung Kim; Pooler, Emilie; Sova, Lorraine; Faulkner-Bond, Molly
ABSTRACT: Scaffolding, an instructional strategy for providing support until learners can perform a task on their own, holds a potential to improve assessments for test takers who need support to demonstrate their abilities, such as English learners (ELs). In this study, we evaluated the benefits of including scaffolded tasks in standardized speaking assessments for young ELs. Our focus was on scaffolded retell tasks that require test takers to retell a given story with procedural scaffolds. We collected responses from 233 third grade ELs to two scaffolded retell tasks, and investigated the relationship between the pre- and post-scaffolding retell performances to learn the impact of the scaffolding on the post-scaffolding performance. We also examined the psychometric added-value of the scaffolding steps and post-scaffolding responses through an application of item response theory (IRT) measurement models. The findings showed that, conditional on the pre-scaffolding performance, the EL test takers' performance on the scaffolding steps were positively associated with their post-scaffolding retell performance. Moreover, the responses to the scaffolding steps and the post-scaffolding retell provided additional information about test takers' oral English proficiency. These findings provide empirical support for the benefits of using scaffolding for EL assessments in a standardized setting.